2022
DOI: 10.1002/ctm2.937
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell RNA sequencing reveals localized tumour ablation and intratumoural immunostimulant delivery potentiate T cell mediated tumour killing

Abstract: Background Metastatic breast cancer poses great challenge in cancer treatment. N‐dihydrogalactochitosan (GC) is a novel immunoadjuvant that stimulates systemic immune responses when administered intratumourally following local tumour ablation. A combination of photothermal therapy (PTT) and GC, referred to as localized ablative immunotherapy (LAIT), extended animal survival and generates an activated B cell phenotype in MMTV‐PyMT mouse mammary tumour microenvironment (TME). However, how T cell pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 96 publications
2
16
0
Order By: Relevance
“…However, we also found that GC did not cause direct, non-specific activation of T cells, but instead works through the activation the APCs (data not shown). To determine the critical roles of dendritic cells (DCs) in antigen presentation, T cell activation and differentiation, and effector and memory T cell formation, we discovered the pathways of T cell activation through DC activation, consistent with previous published results 42, 43 . We have previously shown that GC directly induces maturation of dendritic cells via increased co-stimulatory molecules CD80, CD40 and MHC-II 44 .…”
Section: Discussionsupporting
confidence: 86%
“…However, we also found that GC did not cause direct, non-specific activation of T cells, but instead works through the activation the APCs (data not shown). To determine the critical roles of dendritic cells (DCs) in antigen presentation, T cell activation and differentiation, and effector and memory T cell formation, we discovered the pathways of T cell activation through DC activation, consistent with previous published results 42, 43 . We have previously shown that GC directly induces maturation of dendritic cells via increased co-stimulatory molecules CD80, CD40 and MHC-II 44 .…”
Section: Discussionsupporting
confidence: 86%
“…We previously reported the promising therapeutic effects of localized ablative immunotherapy (LAIT) on MMTV-PyMT breast tumors and uncovered the anti-tumor roles of tumor-infiltrating B cells 24 and T cells 25 in response to LAIT. Although there are many other reports revealing the transcriptional atlas and anti-tumor roles of both innate and adaptive immune cells by scRNAseq, the contributions of NK cells were less known.…”
Section: Scrna-seq Reveals Heterogeneity Of Tumor-infiltrating Natura...mentioning
confidence: 99%
“…We have previously developed a localized ablative immunotherapy (LAIT) that combines local photothermal therapy (PTT) and intratumoral injection of a novel immunoadjuvant, Ndilydrogalactochitosan (GC). LAIT extended animal survival in the mouse MMTV-PyMT mammary tumor model 22 as well as B16-F10 melanoma model. 23 Using single-cell RNA sequencing (scRNAseq), we showed that LAIT activates sustainable adaptive antitumor responses by increasing the proportions of naïve CD8 + T-cells and memory CD4 + T-cells from a resting state to an activated state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using RNA sequencing analyses, we examined the immune cells within the TME following intratumoral application of GC and found that GC drove a strong type I interferon (IFN) response in both innate and adaptive tumor-infiltrating leukocytes (TILs). The major immune stimulation in ablation-GC treatment was potentiated by GC (18,19). However, only the combination of ablation and GC was able to achieve sustained tumor regression in both treated tumors and untreated distant metastases (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%